Child Neglect After Divorce: Perspective of Child Protection Law and Compilation of Islamic Law - Dewi Ervina Suryani; Pagar Pagar; Muhammad Iqbal Irham (Rechtsvinding, 2026)
This study aims to analyze child neglect following parental divorce from the perspectives of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 on Child Protection (UUPA) and the Compilation of Islamic Law (KHI). This research employs a normative juridical approach. Through qualitative methods, the study finds a highly contrasting difference in perspectives between the UUPA and KHI regarding the issue of child neglect after parental divorce. The UUPA views such actions as a criminal offense, and the perpetrators are subject to legal sanctions. In contrast, the KHI considers child neglect after divorce as an internal civil matter between parents and children, and therefore does not recognize criminal sanctions. Meanwhile, the Religious Court, as a special judicial body that adjudicates divorce cases for Muslim citizens, applies the KHI as its legal basis. Based on these findings, it is concluded that the increase in child neglect parallels the rising number of divorces due to these differing perspectives in addressing the issue. As a result, there is no clear legal certainty serving as a specific reference for resolving cases of child neglect after divorce. In this regard, the author proposes several recommendations: (1) there should be a harmonization of perspectives between the UUPA and KHI concerning child neglect after divorce, recognizing that such acts may result in criminal sanctions; (2) the Supreme Court is encouraged to issue a regulation (PERMA) requiring judges in Religious Courts to include children’s post-divorce rights in their legal considerations even if not explicitly requested, and to impose penalties on parents who fail to comply with such rulings; and (3) the government is advised to establish a special institution or supervisory service unit to monitor child support obligations.